An Analysis of the Inflorescences in species of Luziola (Oryzeae - Poaceae) - Vegetti, Abelardo Carlos (2001)
The inflorescences of Luziola peruviana, L. bahiensis, L. pittieri, L. doelliana and L. gracillima are analyzed typologically as a contribution to the knowledge of inflorescences within the tribe Oryzeae. The inflorescence of Luziola is polytelic. h the paracladial zone, short and long paraclades can be distinguished. In the subzone of long paraclades two regions are present: one with and one without trophotagma. The main florescence, the subzone of short paraclades, and the region of long paraclades without trophotagma form the "flowering unit". Additional long paraclades with trophotagma originate below these units. Each long paraclade with trophotagma repeats the structure observed on the main axis, and ends in a "flowering unit". Several features distinguish long paraclades with trophotagma from the flowering unit of the main floral axis: 1) they are generated by axillary buds developing from the axils of frondose leaves, 2) they bear a developed prophyll at the base, and 3) all spikelets have pistillate flowers.L. pittieri, L. doelliana and L. gracillima are analyzed typologically as a contribution to the knowledge of inflorescences within the tribe Oryzeae. The inflorescence of Luziola is polytelic. h the paracladial zone, short and long paraclades can be distinguished. In the subzone of long paraclades two regions are present: one with and one without trophotagma. The main florescence, the subzone of short paraclades, and the region of long paraclades without trophotagma form the "flowering unit". Additional long paraclades with trophotagma originate below these units. Each long paraclade with trophotagma repeats the structure observed on the main axis, and ends in a "flowering unit". Several features distinguish long paraclades with trophotagma from the flowering unit of the main floral axis: 1) they are generated by axillary buds developing from the axils of frondose leaves, 2) they bear a developed prophyll at the base, and 3) all spikelets have pistillate flowers.L. gracillima are analyzed typologically as a contribution to the knowledge of inflorescences within the tribe Oryzeae. The inflorescence of Luziola is polytelic. h the paracladial zone, short and long paraclades can be distinguished. In the subzone of long paraclades two regions are present: one with and one without trophotagma. The main florescence, the subzone of short paraclades, and the region of long paraclades without trophotagma form the "flowering unit". Additional long paraclades with trophotagma originate below these units. Each long paraclade with trophotagma repeats the structure observed on the main axis, and ends in a "flowering unit". Several features distinguish long paraclades with trophotagma from the flowering unit of the main floral axis: 1) they are generated by axillary buds developing from the axils of frondose leaves, 2) they bear a developed prophyll at the base, and 3) all spikelets have pistillate flowers.h the paracladial zone, short and long paraclades can be distinguished. In the subzone of long paraclades two regions are present: one with and one without trophotagma. The main florescence, the subzone of short paraclades, and the region of long paraclades without trophotagma form the "flowering unit". Additional long paraclades with trophotagma originate below these units. Each long paraclade with trophotagma repeats the structure observed on the main axis, and ends in a "flowering unit". Several features distinguish long paraclades with trophotagma from the flowering unit of the main floral axis: 1) they are generated by axillary buds developing from the axils of frondose leaves, 2) they bear a developed prophyll at the base, and 3) all spikelets have pistillate flowers.3) all spikelets have pistillate flowers.